2012
DOI: 10.1182/blood.v120.21.1592.1592
|View full text |Cite
|
Sign up to set email alerts
|

CD30 Expression in Diffuse Large B-Cell Lymphoma and Its Relation to Important Clinical and Biological Disease Features

Abstract: 1592 Background: CD30 is a well-known diagnostic marker in both anaplastic large cell lymphoma (ALCL) and classical Hodgkin's lymphoma (CHL). Recently the chimeric drug brentuximab vedotin that combines an anti-CD30 monoclonal antibody with the anti-tubulin agent monomethyl auristatin E demonstrated activity in patients with relapsed ALCL and CHL. Previous observational studies have suggested that CD30 may be expressed in 10 to 20% of DLBCLs. It is possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is a positive regulator of apoptosis, and also has been shown to limit the proliferative potential of auto-reactive CD8 effector T cells. CD30 is expressed on malignant cells in classical Hodgkin lymphoma (cHL), anaplastic large cell lymphoma (ALCL), and also on some forms of DLBCL (Campuzano-Zuluaga et al 2012, 1592Slack et al 2012Slack et al , 1558.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a positive regulator of apoptosis, and also has been shown to limit the proliferative potential of auto-reactive CD8 effector T cells. CD30 is expressed on malignant cells in classical Hodgkin lymphoma (cHL), anaplastic large cell lymphoma (ALCL), and also on some forms of DLBCL (Campuzano-Zuluaga et al 2012, 1592Slack et al 2012Slack et al , 1558.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CD30-positive DLBCL (excluding PMBL and GZL) as a group may have better prognosis over CD30 negative cases, but that remains controversial (Hu et al 2013(Hu et al , 2715(Hu et al -2724. The CD30 positive DLBCL cases are more likely to be of non-germinal center origin (Campuzano-Zuluaga et al 2012, 1592Slack et al 2012Slack et al , 1558. It has been shown that non-germinal center origin subtype of DLBCL is less responsive to chemotherapy, but addition of monoclonal antibody rituximab improved outcomes to some extent (Lenz et al 2008(Lenz et al , 2313(Lenz et al -2323.…”
Section: Introductionmentioning
confidence: 99%